The Influence of Employee of Contextual Factors on Training Effectiveness of Technical Employees at Silterra Malaysia Sdn. Bhd - Abdullah, Lin (2012)
One of the key issues for Malaysian companies is the training and development of their employees. Training plays an important role in providing the necessary skills and knowledge to employees so that their competencies can be improved. Therefore, the training provided should be effective so that the knowledge and skills learnt can be applied to the job. The purpose of this study was to identify the contextual factors that affect the Yield Management (YM) training program for technical staff of Silterra Malaysia Sdn. Bhd. (Silterra). In addition, this study investigated the relationship between the contextual factors and the training effectiveness of YM training program. The research framework was designed based on the Kirkpatrick training model although the research had used quantitative measures. The Kirkpatrick training evaluation model outlines four levels of training effectiveness which are Reaction (Level 1), Learning (Level 2), Behavior (Level 3), and Result (Level 4). The research instrument employed in this study was a questionnaire with 90 items designed to answer 28 hypotheses. The questionnaires were distributed to the respondents by the Human Resources staff of Silterra between November 2010 and February 2011. The study found that the contextual factors such as participant, trainer, training material and organization were the only factors that affect the training effectiveness of YM training program at Silterra while other contextual factors such as training program, working environment and technology were immaterial. The results also indicated that participant, trainer, training material and organization had a positive relationship with training effectiveness at different levels of the Kirkpatrick model. However, factors such as training program, working environment and technology did not show any significant relationship with training effectiveness. This study has made some important contributions to the training literature on the semiconductor industry in Malaysia.